Practical guide to quantification of hepatic iron with MRI. - Henninger, Benjamin; Alustiza, Jose; Garbowski, Maciej; Gandon, Yves (European Radiology, 2020)
Our intention is to demystify the MR quantification of hepatic iron (i.e., the liver iron concentration) and give you a step-by-step approach by answering the most pertinent questions. The following article should be more of a manual or guide for every radiologist than a classic review article, which just summarizes the literature. Furthermore, we provide important background information for professional communication with clinicians. The information regarding the physical background is reduced to a minimum. After reading this article, you should be able to perform adequate MR measurements of the LIC with 1.5-T or 3.0-T scanners. KEY POINTS: • MRI is widely accepted as the primary approach to non-invasively determine liver iron concentration (LIC). • This article is a guide for every radiologist to perform adequate MR measurements of the LIC. • When using R2* relaxometry, some points have to be considered to obtain correct measurements-all explained in this article.